Microtoponymy of Berkovo village near Prekoruplje - Jašović, Golub M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This paper deals with the microtoponymy of the Berkovo village, which is situated on the left bank of Beli drim, in the area called Prekoruplje. Its accurate location is between Ozdrim and Pećka Bistrica confluence with the Drim. Research materials have been recorded by interviewing locals in the year of 1997 (Orthodox Serbs and Catholic Albanians). Some of the entries that are used in this paper, concerning village Berkovo, are taken from the work of Mileta Bukumirić called Onomastic of Prekoruplje (second part). The paper was published in Belgrade in the Onomatology contributions in 1982.
Keywords: Prekoruplje; Berkovo; dromonym; oronym; hydronymy; toponymy